2024
DOI: 10.7554/elife.85753
|View full text |Cite
|
Sign up to set email alerts
|

MTL neurons phase-lock to human hippocampal theta

Daniel R Schonhaut,
Aditya M Rao,
Ashwin G Ramayya
et al.

Abstract: Memory formation depends on neural activity across a network of regions, including the hippocampus and broader medial temporal lobe (MTL). Interactions between these regions have been studied indirectly using functional MRI, but the bases for interregional communication at a cellular level remain poorly understood. Here we evaluate the hypothesis that oscillatory currents in the hippocampus synchronize the firing of neurons both within and outside the hippocampus. We recorded extracellular spikes from 1,854 si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
3
3
0
Order By: Relevance
“…2C ). This finding replicates previous observations of strong theta-phase locking in the human medial temporal lobe ( 34 , 36 ) and indicates that there is a tight temporal relationship between single-neuron activity and local low-frequency activity in the human medial temporal lobe.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2C ). This finding replicates previous observations of strong theta-phase locking in the human medial temporal lobe ( 34 , 36 ) and indicates that there is a tight temporal relationship between single-neuron activity and local low-frequency activity in the human medial temporal lobe.…”
Section: Resultssupporting
confidence: 91%
“…These studies showed that, during a virtual spatial navigation task, neurons in widespread brain regions including hippocampus, amygdala, and parahippocampal regions were phase locked to oscillations in the theta-frequency range ( 34 ). Similar to observations in rodents ( 32 , 33 ), theta-phase locking also occurred between neurons in extrahippocampal regions and the hippocampal theta rhythm in patients performing another set of virtual spatial navigation tasks ( 36 ). In a recognition memory task with static images, stronger theta-phase locking was associated with successful memory formation as assessed with spike-field coherence ( 35 ).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“… 2 , 20 A slower theta rhythm directly impacts theories on human brain function, since the slower cycle could allow an increased number of neuronal assemblies to interact and lock to the same cycle. 16 , 21 This could translate to the association of an increased number of items in working memory compared to rodents and thus increased human cognitive flexibility. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%